Biological and morphological notes on Paralipsa gularis (Zeller) (Lepidoptera Galleriidae) (Bollettino di zoologia agraria e bachicoltura, 2024)
Results of research on biological behaviour of Paralipsa gularis (Zeller) (Lepidoptera Galleriidae), are reported. This insect of tropical origin, through commerciai exchanges, has become dangerous to stored products in severa! areas of the world.In the past P. gularis has been found also in Italy as noxious for dried fruit and stored rices; in 1983 an aboundant presence has been observed in Lomellina (Lombardy) where the pest has caused relevant damages also on stored maize.Regarding the morphology, the P. gularis larvae are similar to those of related species Corcyra cephalonica (Stainton) and Aphomia sociella (Linnaeus), while for the adults the morphology is similar only for the last species.In order to clarify these problems and as a contribution to the knowledge of the species a simple taxonomic key is proposed for the identification of the adults, the morphology of male and female genitalia is then studied, finally a description is given of the new born larva.